Composite faced sandwich construction for primary spacecraft structures - Slade, R. (Cranfield University, 1989)
This study investigated the application of fibre reinforced composite materials to spacecraft sandwich structures. In particular, aspects of the manufacture, analysis and design optimisation of components fabricated using the co-cure process were studied. The manufacturing process was developed to ultimately enable a full size thrust tube structure to be built using a single step cure, the design of which was verified by a modal survey test. Techniques for the analysis of stiffness, strength., vibration frequencies and local instability were established and found to correlate well with tests on co-cured sandwich specimens. The current wrinkling theory for composite faced sandwich was extended to the more general case to allow facesheet constitutive matrix coupling and multiaxial loding to be accomodated. The analytical methods were incorporated within simple optimisation schemes, amenable to employment at the preliminary design stage, to allow alternative feasible designs for panel and thrust tube structures to be generated. These illustrated the benefits of the use of composite materials and the co-cure manufacturing technique for spacecraft sandwich components.